PENGGUNAAN KALIMAT INTEROGATIF PADA ANAK USIA 5 TAHUN: KAJIAN PERKEMBANGAN SINTAKSIS - Aisyah, Nisa; Tiara, Mafi Sri Wahyu; Putra, Dona Aji Karunia (Universitas Madura, 2022)
The purpose of this research is to describe the forms of interrogatives used in TK Aisyiyah 56, South Tangerang City. The method used in this research is a qualitative descriptive method. The subjects of this research are 5-year-old children from TK Aisyiyah 56, South Tangerang City. The data collected in this research are speech acts in the form of questions from 5-year-old children. The data collection techniques used in this research are observation and literature review. The researcher is the instrument in this research, analyzing the data obtained from direct observation and interaction with the research subjects. The results of this research show that the types of interrogatives used by 5-year-old children in TK Aisyiyah 56, South Tangerang City consist of the interrogative words 'apa' (what), 'siapa' (who), 'kapan' (when), 'di mana' (where), 'gimana' (how), and 'kenapa' (why). The interrogative sentences with the interrogative word 'apa' were found in 9 data, 'siapa' in 8 data, 'gimana' in 2 data, 'kenapa' in 3 data, 'kapan' in 4 data, and 'di mana' in 4 data. From the data, the most dominant interrogative speech acts used were those using the interrogative words 'apa' and 'siapa'